PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATERI WIRAUSAHA PRODUK KERAJINAN DARI LIMBAH PADA SISWA KELAS XII TKJ 2 SMK NEGERI 1 PANGANDARAN TAHUN PELAJARAN 2019/2020 - Hernawan, Wawan (Wahana Pendidikan, 2021)
Entrepreneurship of decorative handicraft products from waste is one of the materials contained in the subjects of Craft and Entrepreneurship at level XII. The use of traditional learning models in learning the material results in activeness and student learning outcomes are not optimal. The purpose of this study was to describe the learning process through the Project based learning (PjBL) learning model to improve the activeness and learning outcomes of students in class XII TKJ 2 SMK Negeri 1 Pangandaran in the academic year 2019/2020 on Entrepreneurial decoration craft products from waste. The variable that was the target of change in this study was the activeness and learning outcomes of students of class XII TKJ 2 SMK Negeri 1 Pangandaran in the academic year 2019/2020 about entrepreneurship of handicraft decoration products from waste while the action variables used in this study were the Project based learning (PjBL) learning model. The form of this research is classroom action research which takes place in two cycles. Each cycle consists of 4 stages, namely planning, action, observation and reflection. The research subjects were students of class XII TKJ 2 SMK Negeri 1 Pangandaran in the academic year 2019/2020, amounting to 35 people. Data collection techniques used were observation and tests. The data analysis technique used is qualitatively consisting of three main stages, namely data reduction, data exposure and conclusion drawing. The results of this study stated that the Project based learning (PjBL) learning model was proven to be able to increase the activeness and learning outcomes of students of class XII TKJ 2 SMK Negeri 1 Pangandaran in the academic year 2019/2020 on entrepreneurial materials for decoration craft products from waste. The results stated that there was an increase in the level of mastery of the material (average grade) of 8.5%. While an increase in the percentage of mastery learning by 80%. In addition, Project based learning (PjBL) learning model is proven to be able to improve the behavior of students of class XII TKJ 2 when the learning process is taking place. They are more able to actively participate in every learning activity, show motivation and interest to learn, have a sense of togetherness, do tasks enthusiastically, be able to establish harmonious cooperation with group friends, have high self-confidence, follow learning happily, able express ideas / ideas / opinions.